Relationship between the roles of Students’ Councils in Strikes Management Strategies: Case of Public Secondary Schools in Central Kenya - Wanjohi , Esther N.; Kinyanjui , Josphat; Gitumu , Margaret (African Journal of Education,Science and Technology (AJEST), 2019)
The ministry of education has compelled public secondary schools to constitute students representative councils in order to involve learners in decision making process and to provide a forum for students’ voice in school management so as to effectively address students’ problems. However, despite the constitution of students’ councils and their representation in the schools’ Board of Management, school strikes continue unabated and the relationship between school administrators and students remains unenthusiastic in public secondary schools in Central Kenya. The purpose of this study was to find out the relationship between the role of students’ councils and students strikes in public secondary schools. The objectives of the study were to; establish the roles of the students’ council presidents and assess their attitudes towards strike management strategies used by administrators in secondary schools. The study adopted a descriptive survey research design and was guided by Maslow’s theory of hierarchy of needs. The target population consisted of 847 students` council presidents in public secondary schools. The researcher employed simple random sampling technique and Gay’s sampling formula of 10% was used to determine the sample size, therefore 10% of 847 yielded a sample size of 85 respondents. Data was collected using questionnaires and analyzed using descriptive and inferential statistics, aided by computer software SPSS version 21. Analyzed data revealed that the student council presidents were largely unaware of their functions relating to strike management strategies and that they felt left out in the strategies employed by their schools (=3.30 on a scale of 1-5). The study further established that the student council presidents’ attitudes towards strike management strategies used by administrators were negative (=1.71) on the scale used of 1-5. It had been hypothesized that there was no statistically significant relationship between strategies used in strike management and the role of SC presidents. To test the hypothesis, regression analysis was done, which yielded a coefficient of the role of student council presidents in strike management strategies was 0.106 and a t-statics of .330 with a p-value of 0.746. The null hypothesis was thus accepted and it was concluded that the role of student council presidents’ does not significantly influence strike management and thus has a non-significant positive relationship with strike management in schools. Based on the findings of the study, it was recommended that there is need to strengthen students’ councils and sensitize the presidents on their roles in strike management strategies in secondary schools. This implies the need to enforce adherence to the implementation of the student council policy with a view to compel schools to actualize the democratization of management practices in secondary schools in order to incorporate students concerns in decision making processes.